Interactions Between Ephedra sinica and Prunus armeniaca: From Stereoselectivity to Deamination as a Metabolic Detoxification Mechanism of Amygdalin - Yan Qin (Frontiers Media S.A., 2021)
Mahuang–Xingren (MX, Ephedra sinica Stapf-Prunus armeniaca L.) is a classic herb pair used in traditional Chinese medicine. This combined preparation reduces the toxicity of Xingren through the stereoselective metabolism of its main active ingredient amygdalin. However, whether stereoselectivity is important in the pharmacokinetic properties of amygdalin either in the traditional decoction or in the dispensing granules is unclear. Amygdalin is hydrolyzed to its metabolite, prunasin, which produces hydrogen cyanide by degradation of the cyano group. A comprehensive study of the metabolic pathway of amygdalin is essential to better understand the detoxification process. In this article, the potential detoxification pathway of MX is further discussed with regard to herb interactions. In this study, the pharmacokinetic parameters and metabolism of amygdalin and prunasin were investigated by comparing the traditional decoction and the dispensing granule preparations. In addition, several potential metabolites were characterized in an incubation system with rat liver microsomes or gut microbial enzymes. The combination of Xingren with Mahuang reduces exposure to D-amygdalin in vivo and contributes to its detoxification, a process that can be further facilitated in the traditional decoction. From the in vitro co-incubation model, 15 metabolites were identified and classified into cyanogenesis and non-cyanogenesis metabolic pathways, and of these, 10 metabolites were described for the first time. The level of detoxified metabolites in the MX traditional decoction was higher than that in the dispensing granules. The metabolism of amygdalin by the gut microbial enzymes occurred more rapidly than that by the rat liver microsomes. These results indicated that combined boiling both herbs during the preparation of the traditional decoction may induce several chemical changes that will influence drug metabolism in vivo. The gut microbiota may play a critical role in amygdalin metabolism. In conclusion, detoxification of MX may result 1) during the preparation of the decoction, in the boiling phase, and 2) from the metabolic pathways activated in vivo. Stereoselective pharmacokinetics and deamination metabolism have been proposed as the detoxification pathway underlying the compatibility of MX. Metabolic detoxification of amygdalin was quite different between the two combinations, which indicates that the MX decoctions should not be completely replaced by their dispensing granules.